Failing Memory in Nonaffective Psychosis and Prolactin Response to 12.5 µg i.v. TRH - Spoov, Johan; Bredbacka, Per-Erik (Pharmacopsychiatry, 2021)
The increase in plasma prolactin at 15 min following administration of 12.5 µg TRH i. v. (∆prol) was introduced in Pharmacopsychiatry as an inverse estimate of tuberoinfundibular dopamine (TIDA) activity 1. We used the unpublished data set in 20 participants with nonaffective psychosis from our 1991 study utilizing ∆prol 2 and here report new results with its association with memory.